Perancangan Desain Interaksi Modul Informasi Objek Kesehatan Pada Aplikasi Malang Sehat Dengan Menggunakan Metode Human-Centered Design (HCD) - Chika Apsari Dinda; Herman Tolle; Retno Indah Rokhmawati (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2021)
The increase in the number of population is a problem for the local government. This encourages the government to improve the quality of public services, one of which is health information. One of the initiatives undertaken by the Malang City Information and Communication Office is by implementing the Smart city concept in Malang City which is targeted to be realized in 2020. Therefore, it is necessary to create an interaction design of an information system in the form of a mobile application based on health information object. Information object has centralized and integrated by information on the concept of technology with health, thus presenting health information that can be accessed by the public efficiently and effectively. This interaction design design applies the Human-Centered Design (HCD) method which involves users and stakeholders in each stages. The solution design was evaluated by testing using the remote Usability testing technique and System Usability Scale (SUS) qustionnaire on 20 participants who obtained a score of 98% on the aspect of effectiveness, 92% in the aspect of efficiency and 75 in the aspect of user satisfaction based on the results obtained it falls into the â€œAcceptableâ€ category with a grade scale of C that was included in the 'Good' category of adjective ratings.